Peran Decellurarized Dental Pulp Sebagai Kandidat Biomaterial Baru Dalam Regenerasi Pulpa : Tinjauan Literatur - Pratiwi, Ariyati Retno; Salsabila, Dinia Fitri (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Pulp necrosis is one of the main diseases that are most often found in the teeth and mouth. Root canal treatment is the main solution for pulp necrosis, but its implementation can lead to tooth death and recurrent infections. Regenerating the pulp by transplanting scaffolds, stem cells, and growth factors into the root canal is an alternative that can be offered to treat pulpal disease by keeping the teeth vital. Scaffold plays an important role in pulp regeneration, one of which is the ECM scaffold derived from pulp which combines the micro-collagen structure along with bioactive molecules that are important for pulp regeneration and able to promote the differentiation and proliferation of stem cells. This literature review aimed to identify the role of decellularized dental pulp as a new biomaterial candidate in pulp regenerations. The method being used in this review is systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. Decellularized Dental Pulp as a New Biomaterial Candidate has a role in pulp regeneration.